Kesadaran Guru Dalam Meningkatkan Kompetensi Diri di Abad Digital - Enka Nur Jamala Faridi; Lutfi, Ahmad (Journal of Information System and Education Development, 2023)
The industrial revolution has now entered a new round. Namely in industry 4.0. which is characterized by the development of information and communication technology and dominates every line of life, including the learning sector. Critical thinking skills, problem-solving skills and good adaptability are important points in order to face this great technological revolution in the 21st century. However, the rapid development of technology in the 21st century has a lot of impact on the world of education. Teachers in the context of education have a big role because teachers are at the forefront of the implementation of education and face students directly. However, the real conditions are not as few as teachers who still do not have the awareness to improve the self-competence needed in the 21st Century. This study aims to describe how the importance of teacher awareness to improve self-competence in the 21st century. The methodology used is a literature study by describing the real conditions and ideal conditions of 21st century teacher competencies. The results show that teachers must have a strong, high awareness and come from within the teacher to improve competencies in the form of critical thinking competencies, creative, able to collaborate and able to communicate well